Protection of Private, Family, and Intimate Lives - Moroșteș, Anca Florina (Journal of Legal Studies, 2023)
The Constitutional Court of Romania (CCR) holds an essential position in guaranteeing the observance of human rights within the country's constitutional and legal framework. Through its attribution to interpret and verify the compliance of laws with the Constitution, the CCR has built a vast and particularly significant caselaw regarding the individual’s fundamental rights.By studying the Constitutional Court of Romania's judicial practice in the field of human rights, we can examine how fundamental rights are interpreted and implemented in the national legal system.In this regard, the CCR plays a vital role in ensuring the protection and promotion of these rights by interpreting the Constitution and applicable legislation in accordance with international standards.It is important to highlight that the CCR's human rights caselaw reflects the constant attempt to ensure a balance between the individual’s and society's interests, protecting fundamental rights in accordance with the principles of the rule of law and international standards in the field.Through the analysis of concrete cases and constitutional interpretation, the CCR strengthens its essential role in human rights promotion and defense in Romania.